PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 40 PADANG - Wandila, Sephia; Yerizon, Yerizon (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students need mathematical problem solving skills to trace the stages and find the desired solution in mathematics. However, in the 2023/2024 academic year, grade VIII students at SMP Negeri 40 Padang still had low ability in solving mathematical problems. The test data shows this. We are interested in adopting Problem Based Learning (PBL) as a learning model. Research was conducted to compare the Problem Based Learning model with direct learning to improve students' mathematics problem solving skills. This study used the Nonequivalent Posttest-Only Control Group Design. We used random sampling methodology. The experimental group consisted of students of class VIII.1, while the control group consisted of students of class VIII.3. The Mann-Whitney test confirmed the research hypothesis. Data analysis showed a P-value of 0.002, which indicated statistical significance. The null hypothesis H0 was rejected because the P-value was less than α = 0.05. Problem-based learning improved mathematical problem solving ability more significantly than direct learning. Keywords – Mathematical problem solving ability, PBL, Direct learning